Menangkal Radikalisme Agama di Sekolah - Abdul Munip (Jurnal Pendidikan Islam, 2012)
It is undeniable that some Indonesian Muslims understand Islam in a radicalism perspective. They used several means to disseminate this radicalism through the organization of cadres, speeches in mosques are managed by their control, publishing magazines, booklets and books, and through various websites on the internet. As a result, Islamic radicalism has entered the most schools in some areas. If this is not immediately anticipated, it can help in growing the intolerance attitudes among students as opposed to the purpose of religious education itself.